"Tear drops" in the cerebrospinal fluid: Correct by scatter, but pathognomonic by site. Issue 3 (26th September 2014) - Mittal, Reena; Chopra, Anita; Soni, Sushant; Bakhshi, Sameer; Kumar, Rajive
Abstract : Extramedullary relapse in acute promyelocytic leukemia (APL) is rare, but occurs most commonly in central nervous system (CNS), generally in high‐risk cases (total leucocyte count ≥10, 000/µL, atypical morphology or disseminated intravascular coagulation at presentation), and concomitant with bone marrow (BM) relapse. Here, we describe a case of APL who except for CD56 positivity was low risk but had a CNS relapse without concomitant BM involvement. Diagnosis of isolated CNS relapse was based on characteristic tear‐drop pattern for CD45/side scatter plot on flow cytometry, a full compatible immunophenotype and cytomorphology in the cerebrospinal fluid. The case illustrates the value of the latter and the importance of including CD56 in risk assessment of APL. © 2014 International Clinical Cytometry Society